Os “cinemas de rua” no espaço urbano de João Pessoa: surgimento e apogeu (1897 - 1970) - Oliveira, Elisa Beatriz Carneiro (2024)
The work is based on the understanding of a relationship between movie theaters and urban space. Understanding that such equipment is part of an urban context of modernization, the research aims to investigate the link between cinema exhibition activities, as a cultural component of urban dynamics, with the city, between the period of 1897, the arrival of cinema in city, and 1970, the end of its heyday. Analyzing the socio-spatial transformations that the habit of attending cinemas produces, based on the case study of the city of João Pessoa/PB, it is identified that the appearance and description of “street cinema” theaters had great relevance in the production of a more active urban social life in the capital of Paraíba, coinciding with the reform process that was taking place in most Brazilian cities. Relying on Lefebvre's methodological approach to the production of space and a theoretical contribution based on the spatio-temporal processes of cinemas, a historical trajectory of these theaters in the city's space was constructed, identifying two main moments: the first corresponds to the insertion and development of cinema in a city that was experiencing a process of urban modernization; and the second is marked by the period from August with greater activity in cinemas until when theaters begin to decline, a moment in which the city begins its most blatant expansion. This historical path is supported by bibliographic research on the urban modernization process of João Pessoa, in hemerographic research as a way of understanding the socio-spatial dynamics of cinemas during the same period, as well as in the construction of a mapping of theaters in each decade of cinema study. dissertation.